2011
DOI: 10.1007/s00482-011-1092-6
|View full text |Cite
|
Sign up to set email alerts
|

Die deutsche Version des Parents‘ Postoperative Pain Measure (PPPM-D)

Abstract: The results of this study provide evidence of the reliability, validity and high acceptance of the PPPM-D as an assessment tool of postoperative pain among children aged 2 through to 12 years of age after orthopedic or trauma surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…(18) Çocuklarda ebeveynlerin postoperatif dönemde ağrı değerlendirmesi amacıyla yapılan bir ölçek çalışmasında ise, 2-4 yaş grubundaki çocuklar için paralel form olarak yüz ifadeleri ağrı ölçeğinin kullanıldığı ve yüz ifadeleri ağrı ölçeğini kullanarak değerlendirmeyi ebeveynlerin yaptığı bildirilmektedir. (19) Wong Baker Ağrı Yüz Değerlendirme Tablosu için hemşire çocuğa ölçeği nasıl kullanacağını öğretip sonrasında değerlendirme yapmasını istemektedir. Her ne kadar bireysel ifade ölçeği olarak gösterilse de hemşire ölçeğin kullanımında yer almaktadır.…”
Section: Ağrı Yüz Değerlendirme Tablosu (Wong Baker öLçeği)unclassified
“…(18) Çocuklarda ebeveynlerin postoperatif dönemde ağrı değerlendirmesi amacıyla yapılan bir ölçek çalışmasında ise, 2-4 yaş grubundaki çocuklar için paralel form olarak yüz ifadeleri ağrı ölçeğinin kullanıldığı ve yüz ifadeleri ağrı ölçeğini kullanarak değerlendirmeyi ebeveynlerin yaptığı bildirilmektedir. (19) Wong Baker Ağrı Yüz Değerlendirme Tablosu için hemşire çocuğa ölçeği nasıl kullanacağını öğretip sonrasında değerlendirme yapmasını istemektedir. Her ne kadar bireysel ifade ölçeği olarak gösterilse de hemşire ölçeğin kullanımında yer almaktadır.…”
Section: Ağrı Yüz Değerlendirme Tablosu (Wong Baker öLçeği)unclassified
“…The original PPPM has been developed to assess postoperative pain by parents at home after outpatient surgeries, but the PPPM-D has also been used for inpatients previously. 9 Validation studies have identified the following thresholds for children's pain: CHIPPS score ≥4 in the recovery room and PPPM-D score ≥6 in the first two postoperative days. 5,7,9,10 We evaluated the analgesia quality in hospitalized children after tonsil surgery between 2014 and 2018.…”
Section: Introductionmentioning
confidence: 99%
“…9 Validation studies have identified the following thresholds for children's pain: CHIPPS score ≥4 in the recovery room and PPPM-D score ≥6 in the first two postoperative days. 5,7,9,10 We evaluated the analgesia quality in hospitalized children after tonsil surgery between 2014 and 2018. In children up to 59 months of age, pain intensity was measured with CHIPPS and PPPM-D simultaneously three times daily.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PPPM has been translated into German (24), Finish (25), Swedish (Ljungman, 2002 unpublished data) and Korean (26).…”
Section: Introduction and Rationalementioning
confidence: 99%